CO2 hydrates as a climate change mitigation strategy: definition of stability zones in the Portuguese deep offshore - Bernardes, Luís (2014)
Storage of CO2 as hydrates in sub-seabed sediments has been indicated as an alternative solution for the geological storage of CO2, suitable for offshore areas where large ocean depths and low temperatures exist at short distance from the shore. This paper presents the works conducted to identify the CO2 hydrates stability zone, i.e., the areas where CO2 hydrates may form and remain stable, in the deep offshore of Portugal. The methodology involved building maps of geothermal gradient, seabed temperature, detailed bathymetry and conversion to hydrostatic pressure, and maps of sediment thickness. These data were integrated in a GIS environment and a Fortran code was implemented to compute the thickness of the hydrate stability zone, based on the pressure and the temperature conditions in the sub-seabed sediments. Preferential areas, where further studies should be conducted, are delineated.